Assessing Online Consultation in Participatory Governance: Conceptual framework and a case study of a national sustainability‐related consultation platform in Germany. (24th November 2014) - Schulz, Daniel; Newig, Jens
Abstract Experimenting with different forms of public participation in environmental governance, online consultation has become a widely used instrument. While these new forms of participatory mechanisms have attracted considerable scientific interest, research still remains fragmented and largely disconnected from mainstream literature on participatory governance. This article seeks to close this gap by developing an analytical framework that utilizes this literature to bring together formerly isolated findings in the new field of online participation. This framework is subsequently applied to the empirical case of an online consultation called 'Mitreden‐U' conducted by the German Federal Ministry of the Environment in 2010. By relating key categories of established concepts (e.g. empowerment, participant selection, information flow), the framework allows us to examine the specific opportunities and challenges of online participation. Findings show that while online participation mechanisms have potential to open up governance structures and provide a venue for meaningful interaction, they also require careful design considerations as well as a cultural change on behalf of public administrators. Copyright © 2014 John Wiley & Sons, Ltd and ERP Environment